2022
DOI: 10.1111/dom.14811
|View full text |Cite
|
Sign up to set email alerts
|

The glucose tolerance test in mice: Sex, drugs and protocol

Abstract: Aim: To establish the impact of sex, dosing route, fasting duration and acute habituation stress on glucose tolerance test (GTT) measurements used in the preclinical evaluation of potential glucose-modulating therapeutics.Methods: Adult male and female C57Bl/6J mice, implanted with HD-XG glucose telemetry devices, were fasted for 16 hours or 6 hours following acute habituation stress due to whole cage change, cage change with retention of used bedding or no cage change prior to intraperitoneal (IP) GTTs. To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
(135 reference statements)
3
13
0
Order By: Relevance
“…Chidamide-treated females showed a trend towards improved glucose tolerance ( t (8) = 1.38, p = 0.21), but this did not reach significance ( Figure 1 A). Of note, females displayed greater variability in glucose tolerances, with AUC ranging from 200 to nearly 600, which may be due to hormonal variations [ 29 ]. A recent study reported female mice to be more glucose-tolerant than males and less sensitive to blood glucose fluctuations than males given various stressors [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chidamide-treated females showed a trend towards improved glucose tolerance ( t (8) = 1.38, p = 0.21), but this did not reach significance ( Figure 1 A). Of note, females displayed greater variability in glucose tolerances, with AUC ranging from 200 to nearly 600, which may be due to hormonal variations [ 29 ]. A recent study reported female mice to be more glucose-tolerant than males and less sensitive to blood glucose fluctuations than males given various stressors [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…71,72 Nevertheless, compared with male mice, female mice showed different susceptibilities and responses under various experimental conditions because of hormonal fluctuations, such as being less glucose-intolerant and insulin-resistant. 73,74 In addition, our in vitro validation studies have shown that the genes TEAD1, MYO7A and NDUFC2 were associated with the insulin signalling pathway and hepatic glucose metabolism; however, their detailed regulatory mechanisms still need further study in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have discussed key factors that can affect glucose metabolism, such as fasting duration and sex of the rodents. Other factors that may cause stress and alter glucose metabolism have begun to be described in the literature, such as temperature, method of cage change, and even the sex of the scientist ( Sorge et al 2014 , Drucker 2016 , Georgiou et al 2022 , Kennard et al 2022 ). Regarding the latter, stress responses in mice vary depending on the sex of the investigator handling the mice and merely because men and women give off different scents ( Sorge et al 2014 , Georgiou et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%